If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x-3=-3(x-2)
We move all terms to the left:
-5x-3-(-3(x-2))=0
We calculate terms in parentheses: -(-3(x-2)), so:We get rid of parentheses
-3(x-2)
We multiply parentheses
-3x+6
Back to the equation:
-(-3x+6)
-5x+3x-6-3=0
We add all the numbers together, and all the variables
-2x-9=0
We move all terms containing x to the left, all other terms to the right
-2x=9
x=9/-2
x=-4+1/2
| -9x-8=0 | | 80=33x+1 | | -14+15p=6p-8 | | b/2+1/7=13 | | 2a+1=4a-3 | | 5(a-2)=2a+17 | | -6x-8x=-6-5x+2-8x | | 11/23=24/x | | 1x=-4x+12 | | 4t/5+3=11 | | -x-71=49+7x | | 13m-(-4)=-40 | | -14+5p=6p-8 | | 14+4k=−2k | | F(2a)=2(2a)^2-3(2a)+7 | | 2x+44=5+38 | | -8x^2+68x+220=0 | | 21=x/8+4 | | x+80=x+120 | | 5–6h=-4–7h | | a-2+3=-2* | | -71+10x=73+x | | -6=m+(-3.42 | | 11+10/x=50 | | 2(3t+1)= | | 1/2x+12=8x | | 6x+12=2×-4 | | 4x+2(27-x)=84 | | 4x+12=10x-26 | | |-6x+9|=21 | | a-0.05a=760 | | 3(7x+13)12x+15=2 |